Proving Incentives for Long-Term Investment by Pension Funds : The Use of Outcome-based Benchmarks - Stewart, Fiona (World Bank, Washington, DC, 2014)
A fundamental goal of any pension system is to ensure that members receive an adequate income when they retire. Although traditional defined benefit pension plans set out how pension income will be determined in advance and then strive to deliver this, the growing number of defined contribution plans accumulate a sum of assets which can then be turned into a pension income on retirement. However, the amount of this retirement income is not predefined This frequently leads to a focus by not only most pension providers, but also regulators and pension plan members themselves on the short-term accumulation of pension assets rather than the longer-term goal of securing an adequate retirement income. This paper discusses a possible solution to this challenge: the use of benchmarks to encourage pension funds to invest with the longer-term goal of delivering adequate retirement income in mind. Examples are provided of leading pension funds that already work with long-term, outcome-based benchmarks. The paper suggests a methodology for pension regulators to use in order to incentivize pension funds in their jurisdictions to adopt a similar approach.